From Poland to Canada: Memories of Communist Poland and Migration to Canada in Three Texts by Polish-Born Migrant Women Writers - Drewniak, Dagmara (Porównania, 2022)
Canadian ethnic literature has been dominated by testimonies of migrant experience for a long time. Writers of Eastern European extraction, such as Janice Kulyk Keefer, Eva Hoffman, Eva Stachniak, Lisa Appignanesi or Elaine Kalman Naves to mention just a few, have contributed to the vast body of Canadian migrant literature, giving voice to the quandaries of white, invisible minority migration. As it turns out, the latest texts published by Polish-born Canadian women writers also address the issues of migration and the memory of Communist Poland, which the writers left in the 1980s and early 1990s. The aim of this paper is to look at three selected texts: Giant (2012) by Aga Maksimowska, Lemons (2017) by Kasia Jaronczyk and Was It Worth It. Columbus in Jeans (2019) by Liliana Arkuszewska, all of which are debut novels, and discuss their perception and rendition of Communist Poland, which the authors left behind physically and simultaneously struggled to free from mentally. The narratives chosen for this study, despite substantial differences, bear certain similarities in their treatment of Poland as well as become important commentaries on the status of migrant discourses in North America.